1997
DOI: 10.1149/1.1837416
|View full text |Cite
|
Sign up to set email alerts
|

Densification of Yttria‐Stabilized Zirconia: Impedance Spectroscopy Analysis

Abstract: Yttria‐stabilized‐zirconia samples with fairly narrow pore size distributions give well‐defined microstructure impedance semicircles which can be characterized by a blocking factor αR, a capacitance ratio αC and a frequency ratio αF. On an αR vs. αC diagram, the regimes where either the pores or the grain boundaries are dominant are clearly separated. As expected from the reference model, the αRαF product was found proportional to porosity. The fairly continuous variations of αF from the densification to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
100
1
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(121 citation statements)
references
References 3 publications
15
100
1
5
Order By: Relevance
“…The dielectric constants of the bulk (e b ) calculated from the bulk capacitances (C b = e 0 e b A/L) of the samples are in the range of about 54 to 57, irrespective of different yttrium and aluminium concentrations, suggesting that the dielectric constant is quite concentration insensitive. This is in good agreement with the work by Kleitz and coworkers [14,15], in which the dielectric constant of Y 2 O 3 doped ZrO 2 was found to be about 60, being independent of Y 2 O 3 content. However, lower values ($ 30 to 40) for e b were also reported [16][17][18], the cause for this difference may be the different phys.…”
Section: Resultssupporting
confidence: 93%
“…The dielectric constants of the bulk (e b ) calculated from the bulk capacitances (C b = e 0 e b A/L) of the samples are in the range of about 54 to 57, irrespective of different yttrium and aluminium concentrations, suggesting that the dielectric constant is quite concentration insensitive. This is in good agreement with the work by Kleitz and coworkers [14,15], in which the dielectric constant of Y 2 O 3 doped ZrO 2 was found to be about 60, being independent of Y 2 O 3 content. However, lower values ($ 30 to 40) for e b were also reported [16][17][18], the cause for this difference may be the different phys.…”
Section: Resultssupporting
confidence: 93%
“…Figure 10 shows the variation of relative density of fibers with heat treatment temperature. The relative density of the fibers was as high as 74% just after the drying at 373 K. The relative density increases gradually up to 1273 K, above which it increases abruptly and reaches 97% at 1473 K. This densification behavior of 4 mol % YSZ fibers found in this study coincides with that of 8 mol % YSZ bulk reported by M. C. Stein et al 20) In case of ordinary YSZ bulk sintered body, it has been reported the relative density reaches 95% or more after sintering at 16731773 K for 24 h. In the present study, YSZ fiber with high density is obtained at lower temperatures by 773 K than that of YSZ bulk sintered body. The small particle size of the initial zirconia as well as the unique microstructure of the as-prepared fibers in which the monodispersed zirconia particles are closely packed by self-assembly are considered to be the reason.…”
Section: Microstructures Of Ysz Fiberssupporting
confidence: 90%
“…Studies have found the porosity of the electrolyte effects gas transport to the triple phase boundary (TPB) [3,7]. The TPB is the location where the electrolyte, electrode, and gas phase are in contact.…”
Section: Morphology and Microstructurementioning
confidence: 99%